The war encyclopedia - Henzel, Cynthia Kennedy, 1954- (Minneapolis, Minnesota : Encyclopedias, an imprint of Abdo Reference, 2024)
Since the founding of the United States, wars have shaped the nation's history. This title explores the major conflicts in which the US military has been involved, examining the causes of these wars, how they were fought, and what their results were.
Armed conflict in US history -- American revolution -- War of 1812 -- American Indian wars -- Mexican-American war -- American civil war -- Spanish-American war -- Philippine-American war -- World War I -- World War II -- Korean war -- Vietnam war -- Persian gulf war -- Afghanistan war -- Iraq war.
Includes bibliographical references (page 189) and index.
5-8
1000L
Keywords: War -- Juvenile literature; Military history -- Juvenile literature; United States -- Armed Forces -- Juvenile literature; War; Military history; United States -- Armed Forces; Illustrated works; Encyclopedias